Salud sexual y reproductiva y su influencia con las conductas de riesgo en adolescentes. Unidad Educativa María Luisa de Sotomayor, Recinto El Porvenir, Babahoyo, Los Ríos, octubre 2018 – abril 2019 - Díaz Araujo, Paula Jacqueline (2019)
The adolescent population is a priority throughout the world. At a global level, a considerable number of adolescents are already sexually active before reaching the age of 19, and the vast majority do not use any security against pregnancy, nor against the danger of contracting an ETS. In Ecuador, 16.9% of adolescents aged 15 to 19, and 0.6% of girls aged 12 to 14, are mothers. Pregnancy in young people and adolescents makes it difficult for them to continue their education, since most of them are forced to leave school thanks to cultural and social pressures. That is why the general objective was to identify the relationship between sexual and reproductive health and risky behavior in adolescents of the María Luisa de Sotomayor Educational Unit in El Porvenir Campus in the Babahoyo canton of Los Ríos province in October 2018 - April 2019. In the research, a non-experimental, field, descriptive, cross-sectional, qualitative-quantitative study was conducted. Deductive and analytical methods were also used. Based on the research carried out, it could be determined that the students of the Educational Unit require extensive guidance in sexual and reproductive health because the knowledge they have is not as extensive and is due to the lack of communication they have. the parents with their children.